Vocational Skill Training and Generic Skill of Students with Special Needs in Sekolah Menengah Pendidikan Khas Vokasional Indahpura, Johor - Siti Hajar binti Zakariah; Joseph, Elfanny; Ismail, Lisa Mariam Syawal; Ahmad, Nor Aziah; Tukiran, Nor Anis Intan Aqiah; Baharudin , Nurhayati (Research and Innovation in Technical and Vocational Education and Training, 2022)
This study was conducted to identify the perceptions of students with special needs on Vocational Skills Training, identify generic skills according to the most applied priorities in Vocational Skills Training by Indahpura Vocational Special Education Secondary School, Johor (SMPKVI) and see the perceptions of students with special needs on the mastery of this group in generic skills. The design in this study is to use a quantitative study with a survey method that collects quantitative data through a questionnaire instrument. This questionnaire was adapted from previous studies and modified according to the suitability of this study. The data obtained were analyzed using Statistical Package for The Social Science Version 23 (SPSS) software. The data obtained were also analyzed using descriptive analysis to see the mean score values, percentages and standard deviations. Overall, the findings in this study show that the perception of students with special needs on Vocational Skills Training is at a high level with a mean score value (M = 4.65). Meanwhile, generic skills according to the priorities applied in Vocational Skills Training showed that communication skills got the highest mean score value (M = 4.22). Followed by ethical and moral skills as well as teamwork with the achievement of mean score values, respectively (M = 4.38) and (M = 3.88). For students with special needs perceptions of mastery in generic skills showed a good level with a mean value (M = 4.38) for communication skills, (M = 4.37) for ethics and morals and (M = 3.37) for teamwork. It is hoped that the results of this study can be used as a guide for TVET lecturers to see the generic skills that are less able to be mastered by students with special needs to be improved. At the same time, a guide for employers to see the abilities of students with special needs in mastering generic skills, to be more confident in providing employment opportunities to students with special needs.